Composite positive electrode material, preparation method thereof, positive electrode plate containing composite positive electrode material, battery and electric device

By covering the positive electrode material with M elemental particles and lithium ion conductor materials, an efficient ionic conduction network is built, which solves the cycle and storage performance problems of nickel-rich ternary positive electrode materials, and improves the rate performance and energy density of the battery.

CN119153634AActive Publication Date: 2024-12-17CONTEMPORARY AMPEREX TECHNOLOGY CO LTD

Patent Information

Application Number
CN202310703936.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-06-14
Publication Date
2024-12-17
Estimated Expiration
2043-06-14

AI Technical Summary

Technical Problem

The poor circulation and storage performance of nickel-rich ternary cathode material system batteries limit their application, and the ionic conductivity of existing coating technology is low, resulting in a degradation of rate performance.

Method used

The composite positive electrode material is used, including the positive electrode active material and a cladding layer. The cladding layer is composed of M-containing elemental particles and lithium-ion conductor materials. The lithium-ion conductor material is attached to the surface of M-cellal particles to build an efficient ionic conductive network to suppress lithium residue on the surface. The compound is produced and doped into the positive electrode active material to enhance its ionic conductivity and layer spacing.

Benefits of technology

It significantly improves the battery's cycle performance, storage performance and rate performance, extends the battery's cycle life, and improves the energy density.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119153634A_ABST
    Figure CN119153634A_ABST
Patent Text Reader

Abstract

The invention provides a composite positive electrode material, a preparation method thereof, a positive electrode plate containing the composite positive electrode material, a battery and an electric device. The composite positive electrode material comprises a positive electrode active material and a coating layer, the coating layer coats at least part of the surface of the positive electrode active material, the coating layer comprises a composite material, the composite material comprises particles containing an M simple substance and a lithium ion conductor material attached to the surfaces of the particles containing the M simple substance, and M comprises at least one of S, Se and Te.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of battery technology, and in particular to a composite positive electrode material and a preparation method thereof, a positive electrode sheet containing the same, a battery and an electrical device. Background Art

[0002] Secondary batteries rely on active ions to be reciprocated between the positive and negative electrodes for charging and discharging. Secondary batteries represented by lithium-ion batteries have outstanding features such as high energy density, long cycle life, no pollution, and no memory effect. Therefore, as a clean energy, secondary batteries have gradually spread from electronic products to large-scale devices such as electric vehicles to adapt to the sustainable development strategy of the environment and energy.

[0003] Among them, energy density is considered to be the biggest bottleneck restricting the development of current secondary batteries. Breakthroughs and innovations in materials are of great significance to achieving the technical goal of high energy density. Nickel-rich ternary cathode materials (such as LiNi m Co n M 1-m-n O2, m≥0.6, M is Mn or Al) has become a research hotspot in recent years due to its high reversible capacity and low cost. However, the cycle performance and storage performance of nickel-rich ternary cathode material system batteries are poor, which limits the application of nickel-rich ternary cathode material system batteries. Summary of the invention

[0004] In order to achieve the above-mentioned objectives, the present application provides a composite positive electrode material, which can improve the cycle performance, storage performance and rate performance of the battery containing it; the present application also provides a method for preparing the composite positive electrode material, a positive electrode sheet containing the composite positive electrode material, a battery and an electrical device.

[0005] An embodiment of the first aspect of the present application provides a composite positive electrode material, which includes a positive electrode active material and a coating layer, which is coated on at least a portion of the surface of the positive electrode active material. The coating layer contains a composite material, and the composite material includes particles containing a single substance M and a lithium ion conductor material attached to the surface of the particles containing the single substance M, and M includes at least one of S, Se, and Te.

[0006] Without intending to be limited by any theory or explanation, the composite positive electrode material of the embodiment of the present application includes a positive electrode active material and a coating layer, and the coating layer contains a composite material, which can effectively improve the cycle performance, storage performance and rate performance of the battery. Specifically, the coating layer of the composite positive electrode material includes the above-mentioned particles containing M element. During the processing or storage of the battery, the coating layer can inhibit the contact between the positive electrode active material and the air, thereby inhibiting the generation of residual lithium compounds (RLCs) on the surface; the coating layer of the composite material also includes a lithium ion conductor material attached to the surface of the particles. The lithium ion conductor material can construct a good ion conductive network at the material level, thereby improving the ion transmission rate of the composite positive electrode material. Compared with the technical solution of directly coating the sulfide element on the surface of the positive electrode active material in the related art, the composite positive electrode material of the embodiment of the present application has the advantage of higher ionic conductivity.

[0007] In addition, when the positive electrode active material is a ternary positive electrode material, during the battery formation process, the M single substance can also react with the positive electrode active material, replacing some of the oxygen atoms on the surface of the positive electrode active material, thereby being doped into the positive electrode active material. Compared with oxygen atoms, M atoms have stronger electronegativity and larger atomic radius. Doping into the positive electrode active material can not only enhance the ionic conductivity of the positive electrode active material, but also widen the interlayer spacing of the positive electrode active material and inhibit the migration of lithium ions and transition metal layers. As a result, the cycle stability of the positive electrode active material can also be improved, delaying the voltage drop and capacity decay of the battery.

[0008] Therefore, the composite positive electrode material of the embodiment of the present application is applied to a secondary battery, which can effectively improve the cycle performance, storage performance and rate performance of the battery.

[0009] In any embodiment of the present application, the lithium ion conductor material includes an ion conductivity of 1×10 -5 S / cm or above, and can be selected as a lithium ion conductor material of 0.001S / cm-1S / cm.

[0010] When the ionic conductivity of the lithium ion conductor material meets the given range, it is not only beneficial to improve the ion transmission rate of the composite positive electrode material, but also beneficial to the cation reaction of the M element with the surface of the positive electrode active material, and doping into the positive electrode active material to improve the cycle stability of the positive electrode active material. Therefore, the composite positive electrode material of the embodiment of the present application is applied to the secondary battery, which can further improve the rate performance and cycle performance of the battery.

[0011] In any embodiment of the present application, the lithium ion conductor material includes at least one of lithium zinc germanate, lithium aluminum titanium phosphate, lithium aluminum germanium phosphate, lithium lanthanum titanate, glassy lithium conductive electrolyte powder, and garnet structured lithium conductive electrolyte powder.

[0012] Optionally, the lithium ion conductor material includes at least one of lithium aluminum titanium phosphate and lithium aluminum germanium phosphate.

[0013] The lithium ion conductor material selected from the above types has suitable ion conductivity, which can make the coating layer have higher ion conductivity and make the M element have higher kinetic reaction rate.

[0014] In any embodiment of the present application, the volume distribution particle size Dv50 of the particles containing the M element is ≤ 2 μm, and can be selected to be 0.3 μm-1 μm. This is conducive to the coating layer being more tightly coated on the surface of the positive electrode active material, inhibiting the side reaction between the positive electrode active material and the air, thereby inhibiting the generation of RLCs.

[0015] Optionally, the volume distribution particle size Dv50 of the lithium ion conductor material is ≤100nm, and can be selected as 20nm-50nm. This can increase the contact area between the lithium ion conductor material and the M element and the positive electrode active material, which is conducive to further improving the ion transmission rate of the composite positive electrode material and the kinetic reaction rate of the M element, thereby improving the rate performance and cycle performance of the battery.

[0016] Optionally, the volume distribution particle size Dv50 of the positive electrode active material is 5 μm-15 μm. Thus, the composite positive electrode material can have a higher theoretical gram capacity and a suitable ion transport path, which is conducive to improving the capacity of the composite positive electrode material, thereby improving the energy density of the battery.

[0017] Optionally, the volume distribution particle size Dv50 of the composite positive electrode material is 8 μm-20 μm. Thus, the composite positive electrode material can have a suitable ion transmission path, which is conducive to improving the ion transmission rate of the composite positive electrode material, thereby improving the rate performance of the battery.

[0018] In any embodiment of the present application, based on the total mass of the composite positive electrode material, the mass percentage of the positive electrode active material is 80%-98%, and can be optionally 90%-95%.

[0019] In any embodiment of the present application, based on the total mass of the composite positive electrode material, the mass percentage of particles containing M single substance is 0.02%-5%, and can be optionally 0.05%-2%.

[0020] In any embodiment of the present application, based on the total mass of the composite positive electrode material, the mass percentage of the lithium ion conductor material is 0.01%-1%, and can be optionally 0.05%-1%.

[0021] When the content of each component in the composite positive electrode material meets the given range, the composite positive electrode material can have both a higher theoretical gram capacity and a higher ion conductivity, and can also reduce the risk of RLCs generated on the surface of the positive electrode active material. In addition, when the content of the lithium ion conductor material meets the given range, it can also reduce the risk of gelation of the positive electrode slurry, thereby improving the processability of the composite positive electrode material, and then increasing the production capacity of the battery.

[0022] In any embodiment of the present application, the composite material is attached to the surface of the positive electrode active material through a binder to form a coating layer.

[0023] Optionally, the lithium ion conductor material is attached to the surface of the particles containing the M element via a binder.

[0024] The composite material is attached to the surface of the positive electrode active material through a binder, so that the composite material can be firmly anchored on the surface of the positive electrode active material, thereby improving the interface stability between the coating layer and the positive electrode active material.

[0025] In any embodiment of the present application, the adhesive comprises a castor oil-based UV oligomer adhesive.

[0026] Optionally, the castor oil-based UV oligomer adhesive includes a castor oil-based UV oligomer having a molecular weight of 200Da-800Da.

[0027] Castor oil-based UV oligomer binders not only have good bonding properties, but also can form a tight cross-linking network after UV curing, thereby improving the cohesion of the positive electrode film layer. As a result, not only the structural stability of the composite positive electrode material can be improved, but also the structural stability of the positive electrode sheet can be improved, thereby improving the cycle performance of the battery and extending the cycle life of the battery. In addition, castor oil-based UV oligomer binders also have good electrical conductivity. As a result, the electron transfer rate of the composite positive electrode material can be improved, thereby reducing the bulk impedance of the composite positive electrode material, thereby improving the cycle performance, storage performance and rate performance of the battery.

[0028] In any embodiment of the present application, the positive electrode active material includes a nickel-cobalt-manganese ternary material and / or a nickel-cobalt-aluminum ternary material.

[0029] Optionally, in the nickel-cobalt-manganese ternary material, the molar content of Ni element in the transition metal elements is greater than or equal to 0.6.

[0030] Optionally, in the nickel-cobalt-aluminum ternary material, the molar content of Ni element in the transition metal elements is greater than or equal to 0.6.

[0031] The composite positive electrode material of the embodiment of the present application has a specific coating layer, which can inhibit the generation of RLCs on the surface of the positive electrode active material and improve the ion conductivity of the composite positive electrode material. Therefore, it is conducive to the application of ternary positive electrode active materials with high nickel content in secondary batteries, thereby allowing secondary batteries to have high energy density, good cycle performance, storage performance and rate performance.

[0032] An embodiment of the second aspect of the present application provides a method for preparing a composite positive electrode material, comprising: preparing a composite material, comprising mixing particles containing a single substance M with a lithium ion conductor material, allowing the lithium ion conductor material to adhere to the surface of the particles containing the single substance M to obtain a composite material, wherein M includes at least one of S, Se, and Te; preparing a composite positive electrode material, comprising uniformly mixing the composite material and a positive electrode active material, allowing the composite material to coat at least a portion of the surface of the positive electrode active material to obtain a composite positive electrode material.

[0033] According to the method of the embodiment of the present application, a composite positive electrode material is prepared, including a positive electrode active material and a coating layer, and the coating layer contains a composite material, which can effectively improve the cycle performance, storage performance and rate performance of the battery. Specifically, the coating layer of the composite positive electrode material includes the above-mentioned particles containing M element. During the processing or storage of the battery, the coating layer can inhibit the contact between the positive electrode active material and the air, thereby inhibiting the generation of RLCs; the coating layer of the composite material also includes a lithium ion conductor material attached to the surface of the particles. The lithium ion conductor material can construct a good ion conductive network at the material level, thereby improving the ion transmission rate of the composite positive electrode material. Compared with the technical solution of directly coating the sulfide element on the surface of the positive electrode active material in the related art, the composite positive electrode material prepared according to the method of the embodiment of the present application has the advantage of higher ion conductivity.

[0034] In addition, when the positive electrode active material is a ternary positive electrode material, during the battery formation process, the M single substance can also react with the positive electrode active material, replacing some of the oxygen atoms on the surface of the positive electrode active material, thereby being doped into the positive electrode active material. Compared with oxygen atoms, M atoms have stronger electronegativity and larger atomic radius. Doping into the positive electrode active material can not only enhance the ionic conductivity of the positive electrode active material, but also widen the interlayer spacing of the positive electrode active material and inhibit the migration of lithium ions and transition metal layers. As a result, the cycle stability of the positive electrode active material can also be improved, delaying the voltage drop and capacity decay of the battery.

[0035] Therefore, the composite positive electrode material prepared according to the method of the embodiment of the present application is applied to a secondary battery, which can effectively improve the cycle performance, storage performance and rate performance of the battery.

[0036] In any embodiment of the present application, preparing the composite material comprises: mixing and ball-milling particles containing M element, a lithium ion conductor material and a castor oil-based UV oligomer binder to obtain a slurry containing the composite material.

[0037] The preparation of the composite positive electrode material includes: after uniformly mixing the slurry and the positive electrode active material, curing the castor oil-based UV oligomer binder so that the composite material is coated on at least part of the surface of the positive electrode active material to obtain the composite positive electrode material.

[0038] Castor oil-based UV oligomer binders not only have good bonding properties, but also can form a tight cross-linking network after UV curing, thereby improving the cohesion of the positive electrode film layer. As a result, not only the structural stability of the composite positive electrode material can be improved, but also the structural stability of the positive electrode sheet can be improved, thereby improving the cycle performance of the battery and extending the cycle life of the battery. In addition, castor oil-based UV oligomer binders also have good electrical conductivity. As a result, the electron transfer rate of the composite positive electrode material can be improved, thereby reducing the bulk impedance of the composite positive electrode material, thereby improving the cycle performance, storage performance and rate performance of the battery.

[0039] In any embodiment of the present application, the mass ratio of the particles containing M element to the lithium ion conductor material is 1:0.3-1:0.6.

[0040] Optionally, the mass ratio of the particles containing M element to the castor oil-based UV oligomer binder is 1:0.1-1:0.3.

[0041] When the mass ratio of the particles containing M element to the lithium ion conductor material meets the given range, an appropriate amount of lithium ion conductor material can be attached to the surface of the particles, thereby improving the ionic conductivity of the composite positive electrode material and reducing the risk of RLCs generated on the surface of the positive electrode active material. In addition, when the mass ratio of the particles to the lithium ion conductor material meets the given range, the risk of gelation of the positive electrode slurry can also be reduced, thereby improving the processability of the composite positive electrode material.

[0042] An embodiment of the third aspect of the present application provides a positive electrode plate, including a positive electrode collector and a positive electrode film layer located on at least one side of the positive electrode collector, the positive electrode film layer includes the composite positive electrode material of the first aspect, or the composite positive electrode material prepared according to the method of the second aspect.

[0043] The positive electrode plate of the embodiment of the present application includes the composite positive electrode material of the first aspect, or the composite positive electrode material prepared according to the method of the second aspect, and is applied to a secondary battery, so that the secondary battery can have good cycle performance, storage performance and rate performance.

[0044] A fourth aspect of an embodiment of the present application provides a battery, comprising the positive electrode plate of the third aspect.

[0045] The battery of the embodiment of the present application includes the positive electrode plate of the third aspect, which can have good cycle performance, storage performance and rate performance.

[0046] A fifth aspect of an embodiment of the present application provides an electrical device, comprising the battery of the fourth aspect.

[0047] The electric device of the embodiment of the present application comprises the battery of the fourth aspect, and thus has at least the same advantages as the battery. BRIEF DESCRIPTION OF THE DRAWINGS

[0048] Figure 1 It is a schematic diagram of the structure of a composite positive electrode material in one embodiment of the present application.

[0049] Figure 2 It is a schematic structural diagram of a composite positive electrode material in another embodiment of the present application.

[0050] Figure 3 It is a schematic diagram of an implementation of a battery cell of the present application.

[0051] Figure 4 yes Figure 3 An exploded view of an embodiment of a battery cell of the present application is shown.

[0052] Figure 5 It is a schematic diagram of an embodiment of a battery module of the present application.

[0053] Figure 6 It is a schematic diagram of an embodiment of the battery pack of the present application.

[0054] Figure 7 yes Figure 6 An exploded view of an embodiment of a battery pack of the present application is shown.

[0055] Figure 8 It is a schematic diagram of an implementation of an electrical device of the present application, and the electrical device may include a battery pack or a battery module according to an embodiment of the present application as a power source.

[0056] 100 composite positive electrode material; 110 positive electrode active material; 120 coating layer; 121 composite material; 121a particles containing M element; 121b lithium ion conductor material; 121c castor oil-based UV oligomer binder; 1 battery pack; 2 upper box; 3 lower box; 4 battery module; 5 battery cell; 51 shell; 52 electrode assembly; 53 cover plate. DETAILED DESCRIPTION

[0057] Hereinafter, the embodiments of the composite positive electrode material and its preparation method, the positive electrode sheet, the battery and the electric device containing the composite positive electrode material of the present application are specifically disclosed with appropriate reference to the accompanying drawings. However, there may be cases where unnecessary detailed descriptions are omitted. For example, there are cases where detailed descriptions of well-known matters and repeated descriptions of actually the same structure are omitted. This is to avoid the following description from becoming unnecessarily lengthy and to facilitate the understanding of those skilled in the art. In addition, the drawings and the following descriptions are provided for those skilled in the art to fully understand the present application and are not intended to limit the subject matter described in the claims.

[0058] "Scope" disclosed in the present application is limited in the form of lower limit and upper limit, and a given range is limited by selecting a lower limit and an upper limit, and the selected lower limit and upper limit define the boundary of a special range. The scope limited in this way can be including end values ​​or not including end values, and can be arbitrarily combined, that is, any lower limit can be combined with any upper limit to form a scope. For example, if the scope of 60-120 and 80-110 is listed for a specific parameter, it is understood that the scope of 60-110 and 80-120 is also expected. In addition, if the minimum range values ​​1 and 2 are listed, and if the maximum range values ​​3, 4 and 5 are listed, the following scope can be all expected: 1-3, 1-4, 1-5, 2-3, 2-4 and 2-5. In the present application, unless otherwise specified, the numerical range "ab" represents the abbreviation of any real number combination between a and b, wherein a and b are real numbers. For example, the numerical range "0-5" means that all real numbers between "0-5" are listed in this document, and "0-5" is just an abbreviation of these numerical combinations. In addition, when a parameter is expressed as an integer ≥ 2, it is equivalent to disclosing that the parameter is, for example, an integer of 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.

[0059] Unless otherwise specified, all embodiments and optional embodiments of the present application can be combined with each other to form a new technical solution.

[0060] Unless otherwise specified, all technical features and optional technical features of this application can be combined with each other to form a new technical solution.

[0061] If there is no special explanation, all steps of the present application can be performed sequentially or randomly, preferably sequentially. For example, the method includes steps (a) and (b), which means that the method may include steps (a) and (b) performed sequentially, or may include steps (b) and (a) performed sequentially. For example, the method may further include step (c), which means that step (c) may be added to the method in any order. For example, the method may include steps (a), (b) and (c), or may include steps (a), (c) and (b), or may include steps (c), (a) and (b), etc.

[0062] If there is no special explanation, the "include" and "comprising" mentioned in this application are open-ended or closed-ended. For example, the "include" and "comprising" may mean that other components not listed may also be included or only the listed components may be included or only the listed components may be included.

[0063] If not specifically stated, in this application, the term "or" is inclusive. For example, the phrase "A or B" means "A, B, or both A and B". More specifically, any of the following conditions satisfies the condition "A or B": A is true (or exists) and B is false (or does not exist); A is false (or does not exist) and B is true (or exists); or both A and B are true (or exist).

[0064] Unless otherwise specified, the values ​​of the parameters mentioned in this application can be measured by various test methods commonly used in the art, for example, they can be measured according to the test methods given in the examples of this application. Unless otherwise specified, the test temperature of each parameter is 25°C.

[0065] Unless otherwise specified, the ratio parameters involved in this application are compared in the same unit. For example, the thickness ratio of A to B is 1.2:1, and the thickness units of A and B are the same.

[0066] With the application and promotion of secondary batteries in various electronic products and new energy vehicles and other industries, higher requirements are placed on the energy density of secondary batteries.

[0067] Nickel-rich ternary cathode materials (such as LiNi m Co n M 1-m-n O2, m ≥ 0.6, M is Mn or Al) has become a research hotspot in recent years due to its high reversible capacity and low cost. Related technologies have involved nickel-rich ternary positive electrode materials with a nickel content of more than 90%, such as LiNi 0.9 Mn 0.1 O2 and LiNi 0.95 Co 0.025 Mn 0.025O2, and obtained a very impressive initial discharge specific capacity.

[0068] However, nickel-rich ternary cathode materials are prone to produce surface residual lithium compounds (RLCs), which are not only electrochemically inactive but also hinder the Li + As well as the diffusion of electrons, this limits the capacity of the nickel-rich ternary positive electrode material, aggravates the growth of the internal resistance of the battery, and deteriorates the cycle performance and storage performance of the battery.

[0069] The relevant technology involves modifying the nickel-rich ternary cathode material to remove RLCs on its surface and inhibit the subsequent formation of RLCs. Among them, surface coating is one of the more commonly used modification strategies. Surface coating can inhibit the contact between the nickel-rich ternary cathode material and the air by forming a coating layer on the surface of the nickel-rich ternary cathode material, thereby inhibiting the formation of RLCs.

[0070] However, the coating layer involved in the related art has low ionic conductivity, which leads to a decrease in the rate performance of the battery.

[0071] In view of this, an embodiment of the present application provides a composite positive electrode material, which can improve the cycle performance, storage performance and rate performance of a battery containing the composite positive electrode material; the present application also provides a method for preparing the composite positive electrode material, a positive electrode sheet containing the composite positive electrode material, a battery and an electrical device.

[0072] Composite cathode materials

[0073] The embodiment of the first aspect of the present application provides a composite positive electrode material, which includes a positive electrode active material and a coating layer, wherein the coating layer is coated on at least a portion of the surface of the positive electrode active material. The coating layer includes a composite material, wherein the composite material includes particles containing a single substance M and a lithium ion conductor material attached to the surface of the particles containing a single substance M, wherein M includes at least one of S, Se, and Te.

[0074] Studies have shown that sulfur elements, such as S, Se, and Te, have strong reducing properties. The transition metals in nickel-rich ternary cathode materials exist in the form of cations. 3+ 、Ni 2+ 、Co 3+ , Mn 4+ When cations such as Li2SO3 and Li2SO4 come into contact with sulfide elements, the sulfide elements can react with these cations to form electrochemically stable compounds (such as Li2SO3, Li2SO4, etc.), thereby forming a coating layer. +It can be used to compensate for the loss of active lithium ions caused by the formation of SEI film during the first charge and discharge cycle; on the other hand, the generated electrochemically stable compounds can play a similar role as CEI film to improve the stability of the positive electrode environment. However, the above-mentioned electrochemically stable compounds, such as Li2SO3, Li2SO4, etc., still have the defect of low ion conductivity, which makes it difficult to improve the rate performance of the battery.

[0075] Without intending to be limited by any theory or explanation, the composite positive electrode material of the embodiment of the present application includes a positive electrode active material and a coating layer, and the coating layer contains a composite material, which can effectively improve the cycle performance, storage performance and rate performance of the battery. Specifically, the coating layer of the composite positive electrode material includes the above-mentioned particles containing M element. During the processing or storage of the battery, the coating layer can inhibit the contact between the positive electrode active material and the air, thereby inhibiting the generation of RLCs; the coating layer of the composite material also includes a lithium ion conductor material attached to the surface of the particles containing M element. The lithium ion conductor material can construct a good ion conductive network at the material level, thereby improving the ion transmission rate of the composite positive electrode material. Compared with the technical solution of directly coating the sulfide element on the surface of the positive electrode active material in the related art, the composite positive electrode material of the embodiment of the present application has the advantage of higher ion conductivity.

[0076] In addition, when the positive electrode active material is a ternary positive electrode material, during the battery formation process, the M single substance can also react with the positive electrode active material, replacing some of the oxygen atoms on the surface of the positive electrode active material, thereby being doped into the positive electrode active material. Compared with oxygen atoms, M atoms have stronger electronegativity and larger atomic radius. Doping into the positive electrode active material can not only enhance the ionic conductivity of the positive electrode active material, but also widen the interlayer spacing of the positive electrode active material and inhibit the migration of lithium ions and transition metal layers. As a result, the cycle stability of the positive electrode active material can also be improved, delaying the voltage drop and capacity decay of the battery.

[0077] Therefore, the composite positive electrode material of the embodiment of the present application is applied to a secondary battery, which can effectively improve the cycle performance, storage performance and rate performance of the battery.

[0078] In an embodiment of the present application, the positive electrode active material may be one or more of the nickel-containing lithium transition metal oxides and their modified compounds for secondary batteries known in the art. Examples of nickel-containing lithium transition metal oxides may include, but are not limited to, one or more of lithium nickel oxide, lithium nickel cobalt oxide, lithium nickel manganese oxide, lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide and their modified compounds having a nickel content of more than 0.6. The above-mentioned "nickel content of more than 0.6" may mean that the molar content of the Ni element is greater than or equal to 0.6 based on the total molar amount of the transition metal element in the nickel-containing lithium transition metal oxide. For example, for lithium nickel cobalt manganese oxide, "nickel content of more than 0.6" may mean that the molar amount of the Ni element / (molar amount of the Ni element + molar amount of the Co element + molar amount of the Mn element) ≥ 0.6.

[0079] In the embodiments of the present application, the lithium ion conductor material may refer to a substance having ionic conductivity, and may specifically include a fast ion conductor material whose conductive ions are lithium. Examples of the lithium ion conductor material may include one or more lithium ion conductor materials known in the art, which are not limited here.

[0080] In the embodiments of the present application, the lithium ion conductor material is attached to the surface of the particle containing the M element, which may mean that the lithium ion conductor material is anchored on the particle surface by interacting with the surface of the particle containing the M element, or is anchored on the particle surface containing the M element by the action of a binder. For example, the lithium ion conductor material may be attached to the surface of the particle containing the M element by chemical bonding or hydrogen bonding, or the lithium ion conductor material may be attached to the surface of the particle containing the M element by a binder.

[0081] Figure 1 FIG. 1 shows a schematic diagram of the structure of a composite positive electrode material according to an embodiment of the present application. Figure 1 As shown, the composite positive electrode material 100 may include a positive electrode active material 110 and a coating layer 120, and the coating layer 120 is coated on at least a portion of the surface of the positive electrode active material 110. The coating layer 120 may include a composite material 121, and the composite material 121 may include particles 121a containing a single substance M and a lithium ion conductor material 121b. The lithium ion conductor material 121b may be attached to the surface of the particles 121a containing a single substance M. In some embodiments, the lithium ion conductor material 121b may be attached to the surface of the particles 121a containing a single substance M, forming a coating layer coated on at least a portion of the surface of the particles 121a containing a single substance M.

[0082] The structure of the composite positive electrode material provided in the embodiments of the present application can be characterized by equipment and methods known in the art. For example, the composite positive electrode material can be subjected to argon ion cross-section polishing, and the cross-section EDS element surface distribution diagram of the composite positive electrode material can be measured by an EDS spectrometer, and the structure of the composite positive electrode material can be determined based on the element distribution in the EDS element surface distribution diagram.

[0083] In some embodiments, the lithium ion conductor material may include an ionic conductivity of 1×10 -5 S / cm or more. For example, the lithium ion conductor material may include an ion conductivity of 1×10 -5 S / cm or more, 1×10 -4 S / cm or more, 0.001S / cm or more, 0.1S / cm or more, or 1S / cm or more lithium ion conductor material.

[0084] Alternatively, in some embodiments, the lithium ion conductor material may include a lithium ion conductor material having an ion conductivity of 0.001 S / cm-1 S / cm. For example, the lithium ion conductor material may include a lithium ion conductor material having an ion conductivity of 0.001 S / cm, 0.005 S / cm, 0.01 S / cm, 0.15 S / cm, 0.2 S / cm, 0.5 S / cm, 0.8 S / cm, 1 S / cm, or a lithium ion conductor material in a range of any two of the above values.

[0085] It is not intended to be limited by any theory or explanation. When the ionic conductivity of the lithium ion conductor material satisfies the given range, the ionic conductivity of the coating layer and the kinetic reaction rate of the M element can be improved. As a result, it is not only beneficial to improve the ion transfer rate of the composite positive electrode material, but also beneficial to the cationic reaction of the M element with the surface of the positive electrode active material, and doping into the positive electrode active material to improve the cycle stability of the positive electrode active material. Therefore, the composite positive electrode material of the embodiment of the present application is applied to a secondary battery, which can further improve the rate performance and cycle performance of the battery.

[0086] Ionic conductivity has a well-known meaning in the art and can be measured by equipment and methods known in the art. For example, the ionic conductivity of a lithium ion conductor material can be determined by its electrochemical impedance spectroscopy (EIS). Specifically, an appropriate amount of lithium ion conductor material can be placed between two stainless steel sheets as blocking electrodes to form a symmetrical battery; the electrochemical workstation used can be DH7001, and the frequency range can be 0.01Hz-106Hz, and the EIS of the lithium ion conductor material at 25°C is tested. The ionic conductivity calculation formula is as follows: δ=L / (R·S), wherein δ is the ionic conductivity (in S / cm), L is the thickness of the lithium ion conductor material between the two stainless steel sheets (in cm), R is the intrinsic resistance of the lithium ion conductor material (in Ω), and S is the effective cross-sectional area of ​​the lithium ion conductor material (in cm). 2 ).

[0087] In some embodiments, the lithium ion conductor material may include at least one of lithium zinc germanate (LISICON structure lithium conductive ceramic powder), lithium aluminum titanium phosphate (LATP), lithium aluminum germanium phosphate (LAGP), lithium lanthanum titanate, glassy lithium conductive electrolyte powder, or garnet structure lithium conductive electrolyte powder.

[0088] Alternatively, in some embodiments, the lithium ion conductor material may include at least one of lithium aluminum titanium phosphate (LAGP) and lithium aluminum germanium phosphate (LAGP).

[0089] Without intending to be bound by any theory or explanation, the lithium ion conductor material selected from the above types has a suitable ionic conductivity, which can make the coating layer have a higher ionic conductivity and make the M element have a higher kinetic reaction rate. Thus, the rate performance and cycle performance of the battery can be further improved.

[0090] In some embodiments, the volume distribution particle size Dv50 of the particles containing the M element is ≤2 μm, for example, it can be 2 μm, 1.8 μm, 1.5 μm, 1.2 μm, 1 μm, 800 nm, 500 nm, 300 nm, 200 nm, or a range consisting of any two of the above values.

[0091] Optionally, in some embodiments, the volume distribution particle size of the particles can also be 0.3μm-1μm, 0.3μm-0.8μm, 0.3μm-0.5μm, 0.4μm-1μm, 0.4μm-0.8μm, 0.4μm-0.6μm, 0.5μm-1μm and the like.

[0092] Without intending to be limited by any theory or explanation, when the particles containing the M single substance have the above-mentioned smaller volume distribution particle size, they generally have a larger specific surface area, thereby increasing the contact area between the composite material and the positive electrode active material. As a result, it is beneficial for the coating layer to be more tightly coated on the surface of the positive electrode active material, inhibiting the side reaction between the positive electrode active material and the air, thereby inhibiting the generation of RLCs. Therefore, the composite positive electrode material of the embodiment of the present application is applied to a secondary battery, which can improve the cycle performance and storage performance of the battery.

[0093] In some embodiments, the volume distribution particle size Dv50 of the lithium ion conductor material is ≤100 nm, for example, it can be 100 nm, 90 nm, 80 nm, 70 nm, 60 nm, 50 nm, 40 nm, 30 nm, 20 nm, 10 nm, or a range consisting of any two of the above values.

[0094] Optionally, in some embodiments, the volume distribution particle size of the lithium ion conductor material can be 20nm-50nm, for example, 20nm, 22nm, 25nm, 28nm, 30nm, 33nm, 36nm, 39nm, 40nm, 41nm, 44nm, 47nm, 50nm, or a range consisting of any two of the above values.

[0095] Without intending to be limited by any theory or explanation, when the lithium ion conductor material has the above-mentioned smaller volume distribution particle size, it generally has a larger specific surface area, thereby increasing the contact area between the lithium ion conductor material and the M element and the positive electrode active material. As a result, it is beneficial to further improve the ion transmission rate of the composite positive electrode material and the kinetic reaction rate of the M element, thereby improving the rate performance and cycle performance of the battery.

[0096] In some embodiments, the volume distribution particle size Dv50 of the positive electrode active material can be 5μm-15μm, for example, it can be 5μm, 6μm, 7μm, 8μm, 9μm, 10μm, 11μm, 12μm, 13μm, 14μm, 15μm, or a range consisting of any two of the above values.

[0097] Without intending to be limited by any theory or explanation, when the volume distribution particle size of the positive electrode active material is within the above suitable range, the composite positive electrode material can have a higher theoretical gram capacity and a suitable ion transport path, thereby being conducive to improving the capacity of the composite positive electrode material, thereby improving the energy density of the battery.

[0098] In some embodiments, the volume distribution particle size Dv50 of the composite positive electrode material can be 8μm-20μm, for example, it can be 8μm, 9μm, 10μm, 11μm, 12μm, 13μm, 14μm, 15μm, 16μm, 17μm, 18μm, 19μm, 20μm, or a range consisting of any two of the above values.

[0099] Without intending to be limited by any theory or explanation, when the volume distribution particle size of the composite positive electrode material is within the above suitable range, it can have a suitable ion transmission path, thereby facilitating the improvement of the ion transmission rate of the composite positive electrode material, thereby further improving the rate performance of the battery.

[0100] The volume distribution particle size Dv50 has a well-known meaning in the art, which can represent the particle size corresponding to when the cumulative volume distribution percentage of the material reaches 50%. The volume distribution particle size Dv50 can be measured by equipment and methods known in the art. The volume distribution particle size Dv50 can be measured by laser diffraction particle size analysis. For example, it can be measured with reference to standard GB / T 19077-2016 using a laser particle size analyzer (e.g., Malvern Master Size 3000).

[0101] In some embodiments, based on the total mass of the composite positive electrode material, the mass percentage of the positive electrode active material may be 80%-98%, and optionally 90%-95%.

[0102] In some embodiments, based on the total mass of the composite positive electrode material, the mass percentage of the particles containing the M element may be 0.02%-5%, and optionally 0.05%-2%.

[0103] In some embodiments, based on the total mass of the composite positive electrode material, the mass percentage of the lithium ion conductor material may be 0.01%-1%, and optionally 0.05%-1%.

[0104] Without intending to be limited by any theory or explanation, when the content of each component in the composite positive electrode material meets the given range, the composite positive electrode material can have both a higher theoretical gram capacity and a higher ion conductivity, and can also reduce the risk of RLCs generated on the surface of the positive electrode active material. In addition, when the content of the lithium ion conductor material meets the given range, it can also reduce the risk of gelation of the positive electrode slurry, thereby improving the processability of the composite positive electrode material, and then increasing the production capacity of the battery.

[0105] In the composite positive electrode material, the mass percentage of the positive electrode active material, the particles containing the M element and the lithium ion conductor material can be measured by equipment and methods known in the art, for example, by inductively coupled plasma emission spectrometry (ICP). Specifically, the elemental analysis can be performed by inductively coupled plasma emission spectrometry (ICP, Ametek, model: SPECTROARCOSICP-OES) with reference to the standards YS / T1006.2-2014, GB / T23367.2-2009 or YS / T1028.5-2015 to determine the composition and content of the elements of the composite positive electrode material, thereby determining the mass percentage of the positive electrode active material, the particles and the lithium ion conductor material.

[0106] In some embodiments, the composite material may be attached to the surface of the positive electrode active material via a binder to form a coating layer.

[0107] Alternatively, in some embodiments, the lithium ion conductor material may be attached to the surface of the particles containing the M element via a binder.

[0108] Without intending to be bound by any theory or explanation, the composite material is attached to the surface of the positive electrode active material through a binder, so that the composite material can be firmly anchored on the surface of the positive electrode active material, thereby improving the interface stability between the coating layer and the positive electrode active material. This is conducive to further reducing the risk of RLCs generated on the surface of the positive electrode active material and improving the cycle stability of the composite positive electrode material, thereby improving the cycle performance and storage performance of the battery.

[0109] Examples of the binder may include one or more binders known in the art, such as but not limited to at least one of polyvinylidene fluoride, polytetrafluoroethylene, sodium carboxymethyl cellulose, and styrene-butadiene rubber. Those skilled in the art may select a suitable binder according to the needs of the actual application, provided that the composite material can be attached to the surface of the positive electrode active material to form a coating layer, and this is not limited here.

[0110] In some embodiments, the adhesive may include a castor oil based UV oligomer type adhesive.

[0111] Alternatively, the castor oil-based UV oligomer-based binder may include a castor oil-based UV oligomer having a molecular weight of 200Da-800Da.

[0112] Without intending to be limited by any theory or explanation, castor oil-based UV oligomer binders have good bonding properties, which can not only make the lithium ion conductor material tightly adhere to the surface of the particles containing the M element and firmly anchor the composite material to the surface of the positive electrode active material, but also make the composite positive electrode material and the positive electrode current collector have good bonding force. In addition, after ultraviolet light curing, castor oil-based UV oligomer binders can also form a tight cross-linked network, thereby improving the cohesion of the positive electrode film layer. As a result, not only the structural stability of the composite positive electrode material can be improved, but also the structural stability of the positive electrode sheet can be improved, thereby improving the cycle performance of the battery and extending the cycle life of the battery. In addition, castor oil-based UV oligomer binders also have good conductive properties. Such as Figure 2 As shown, castor oil-based UV oligomer binder 121c can be distributed between particles of lithium ion conductor material 121b, between composite material 121 and positive electrode active material 110, forming a network with both bonding and conductive properties. Thus, the electron transfer rate of the composite positive electrode material can be improved, thereby reducing the bulk impedance of the composite positive electrode material, thereby improving the cycle performance, storage performance and rate performance of the battery.

[0113] The above molecular weight has a well-known meaning in the art and can be measured by equipment and methods known in the art. For example, it can be measured by mass spectrometer with reference to the test standard GB / T 6041-2020.

[0114] In the embodiments of the present application, the castor oil-based UV oligomer adhesive is a substance known in the art, which may include a castor oil-based UV oligomer, a photoinitiator, and optional additives. The castor oil-based UV oligomer adhesive may be obtained in a variety of ways, such as commercially available, or prepared by methods known in the art.

[0115] As an example, a castor oil-based UV oligomer adhesive can be prepared by the following steps (1) to (3).

[0116] (1) Using a reactive diluent, isocyanate and castor oil as raw materials, reacting until the mass fraction of isocyanate groups in the amount of the raw materials reaches half of the theoretical value before the start of the reaction, thereby obtaining an isocyanate semi-blocked intermediate.

[0117] In step (1), the temperature and time of the reaction are not specifically limited, and those skilled in the art can adjust them according to the reaction materials, feed amount, etc. As an example, the reaction temperature can be 30°C-70°C, and the reaction time can be 2h-7h. The reactive diluent can be selected from at least one of isobornyl methacrylate (IBOMA), tripropylene glycol diacrylate (TPGDA), and 1,6-hexanediol diacrylate (HDDA). Isocyanate can be selected from isocyanates known in the art. In some embodiments, the isocyanate may include one or more diisocyanates. In some embodiments, the molar ratio of isocyanate to castor oil can be (2.7:1)-(2.9:1), and the amount of the reactive diluent can be 10%-40% of the total mass of the reaction materials in step (1).

[0118] (2) mixing the isocyanate semi-blocked intermediate with hydroxy acrylate, adding an antioxidant, allowing the isocyanate semi-blocked intermediate and hydroxy acrylate to react until the isocyanate group content is less than 0.5%, and adding anhydrous ethanol for blocking to obtain a castor oil-based polyurethane acrylic resin.

[0119] In step (2), the temperature and time of the reaction are not specifically limited, and those skilled in the art may adjust them according to the reaction materials, feed amount, etc. As an example, the reaction temperature may be 70°C-100°C, and the reaction time may be 4h-9h. In some embodiments, the hydroxy acrylate may include at least one of hydroxyethyl acrylate (HEA), hydroxypropyl acrylate (HPA), and hydroxypropyl methacrylate (HPMA); the molar ratio of isocyanate to hydroxy acrylate may be (1:1.05)-(1:1.2). The antioxidant may include any one of 2,6-di-tert-butyl-p-cresol (antioxidant 264), pentaerythritol (antioxidant 1000), and 3,5-di-tert-butyl-4-hydroxyphenylpropionic acid octadecyl ester (antioxidant 1076), and the amount may be 0.1%-0.5% of the total mass of the reaction materials.

[0120] (3) Castor oil-based polyurethane acrylic resin, photoinitiator, dispersant and leveling agent are mixed, stirred evenly at 30° C.-50° C. in the dark, and then pigment and defoamer are added and mixed evenly to obtain a castor oil-based UV oligomer adhesive.

[0121] In step (3), the amount of castor oil-based polyurethane acrylic resin, photoinitiator, dispersant and leveling agent added is not specifically limited, and those skilled in the art can adjust it as needed. As an example, the mass ratio of castor oil-based polyurethane acrylic resin, photoinitiator, dispersant, leveling agent, pigment and defoamer can be (80-90): (3-7): (0.1-1): (0.1-1): (1-5): (0.1-0.5).

[0122] As another example, castor oil-based UV oligomer adhesives can also be prepared by a one-pot two-step method. The castor oil-based UV oligomer prepared by the one-pot two-step method has a narrow molecular weight distribution and can have suitable viscosity, excellent bonding properties and good electrical conductivity. The one-pot two-step method can specifically include the following steps (4) to (6).

[0123] (4) 30-50 parts by weight of diisocyanate and 40-50 parts by weight of castor oil are uniformly mixed, and the mixture is heated to 40° C.-50° C. and reacted for 2 h-4 h to obtain an intermediate.

[0124] (5) Add 20-30 parts by mass of hydroxy acrylate, 0.05%-0.15% of the total mass of the reaction raw materials as catalyst and 0.05%-0.2% of the total mass of the reaction raw materials as antioxidant to the intermediate, heat to 70°C-80°C, react for 3h-4h, then add 3%-5% of the total mass of the reaction raw materials as anhydrous ethanol, stir evenly, and obtain a mixture containing castor oil-based UV oligomer. Wherein, the diisocyanate may include one or more diisocyanates known in the art, for example, at least one of isophorone diisocyanate (IPDI), toluene diisocyanate (TDI), diphenylmethane diisocyanate (MDI), p-phenylene diisocyanate (PPDI), and cyclohexane dimethylene diisocyanate (HXDI). The hydroxy acrylate may include at least one of hydroxyethyl acrylate, hydroxypropyl acrylate, and hydroxypropyl methacrylate. The catalyst may include at least one of dibutyltin dilaurate, triethanolamine, bismuth cyclohexane acid, cobalt octoate, and triethylenediamine. The antioxidant may include hydroquinone and / or 2,6-di-tert-butyl-p-cresol.

[0125] (6) The above mixture, photoinitiator, dispersant and leveling agent are mixed, stirred evenly at 30° C.-50° C. in the dark, and then pigment and defoaming agent are added and mixed evenly to obtain a castor oil-based UV oligomer adhesive.

[0126] In step (6), the addition amount of the mixture, photoinitiator, dispersant and leveling agent is not specifically limited, and can be adjusted by those skilled in the art as needed. As an example, the mass ratio of the mixture, photoinitiator, dispersant, leveling agent, pigment and defoamer can be (80-90):(3-7):(0.1-1):(0.1-1):(1-5):(0.1-0.5).

[0127] In some embodiments, the positive electrode active material may include a nickel-cobalt-manganese ternary material and / or a nickel-cobalt-aluminum ternary material.

[0128] Optionally, in the nickel-cobalt-manganese ternary material, the molar content of Ni element in the transition metal elements is greater than or equal to 0.6.

[0129] Optionally, in the nickel-cobalt-aluminum ternary material, the molar content of Ni element in the transition metal elements is greater than or equal to 0.6.

[0130] Without intending to be limited by any theory or explanation, the composite positive electrode material of the embodiment of the present application has a specific coating layer, which can inhibit the generation of RLCs on the surface of the positive electrode active material and improve the ion conductivity of the composite positive electrode material. Therefore, it is conducive to the application of high nickel content ternary positive electrode active materials in secondary batteries, thereby allowing secondary batteries to have high energy density, good cycle performance, storage performance and rate performance.

[0131] Preparation method

[0132] In a second aspect, an embodiment of the present application provides a method for preparing a composite positive electrode material, comprising the following steps S10 to S20.

[0133] S10, preparing a composite material, including mixing particles containing M element with a lithium ion conductor material, allowing the lithium ion conductor material to adhere to the surface of the particles containing M element, to obtain a composite material, wherein M includes at least one of S, Se, and Te.

[0134] In step S10, the lithium ion conductor material can be attached to the surface of the particles containing the M element in a variety of ways. For example, the particles containing the M element can be mixed with the lithium ion conductor material and ball-milled to make the lithium ion conductor material attached to the surface of the particles containing the M element, or the particles containing the M element can be mixed with the lithium ion conductor material and a binder and ball-milled to make the lithium ion conductor material attached to the surface of the particles containing the M element through the binder. Those skilled in the art can select a suitable method according to actual needs, which is not limited here. The lithium ion conductor material can be selected from the lithium ion conductor material described in the first aspect. The implementation method of the lithium ion conductor material has been described and explained in detail above, which will not be repeated here.

[0135] S20, preparing a composite positive electrode material, including uniformly mixing the composite material with the positive electrode active material, and coating the composite material on at least a portion of the surface of the positive electrode active material to obtain the composite positive electrode material.

[0136] In step S20, coating the composite material on at least a portion of the surface of the positive electrode active material can be achieved in a variety of ways. In some embodiments, the composite material, the positive electrode active material and the binder can be evenly mixed so that the composite material is attached to at least a portion of the surface of the positive electrode active material through the binder to form a coating layer. In some embodiments, the composite material and / or the positive electrode active material can also be modified so that the composite material is attached to at least a portion of the surface of the positive electrode active material through chemical bonding to form a coating layer. Those skilled in the art can select a suitable embodiment according to the needs of the actual application, on the premise of satisfying the requirement that the composite material can be attached to the surface of the positive electrode active material to form a coating layer, and are not limited here.

[0137] According to the method of the embodiment of the present application, a composite positive electrode material is prepared, including a positive electrode active material and a coating layer, and the coating layer contains a composite material, which can effectively improve the cycle performance, storage performance and rate performance of the battery. Specifically, the coating layer of the composite positive electrode material includes the above-mentioned particles containing M element. During the processing or storage of the battery, the coating layer can inhibit the contact between the positive electrode active material and the air, thereby inhibiting the generation of RLCs; the coating layer of the composite material also includes a lithium ion conductor material attached to the surface of the particles containing M element. The lithium ion conductor material can construct a good ion conductive network at the material level, thereby improving the ion transmission rate of the composite positive electrode material. Compared with the technical solution of directly coating the sulfide element on the surface of the positive electrode active material in the related art, the composite positive electrode material prepared according to the method of the embodiment of the present application has the advantage of higher ion conductivity.

[0138] In addition, when the positive electrode active material is a ternary positive electrode material, during the battery formation process, the M single substance can also react with the positive electrode active material, replacing some of the oxygen atoms on the surface of the positive electrode active material, thereby being doped into the positive electrode active material. Compared with oxygen atoms, M atoms have stronger electronegativity and larger atomic radius. Doping into the positive electrode active material can not only enhance the ionic conductivity of the positive electrode active material, but also widen the interlayer spacing of the positive electrode active material and inhibit the migration of lithium ions and transition metal layers. As a result, the cycle stability of the positive electrode active material can also be improved, delaying the voltage drop and capacity decay of the battery.

[0139] Therefore, the composite positive electrode material prepared according to the method of the embodiment of the present application is applied to a secondary battery, which can effectively improve the cycle performance, storage performance and rate performance of the battery.

[0140] In some embodiments, preparing the composite material may specifically include: mixing particles containing M element, a lithium ion conductor material, and a castor oil-based UV oligomer binder and ball milling to obtain a slurry containing the composite material.

[0141] The preparation of the composite positive electrode material may specifically include: after uniformly mixing the slurry and the positive electrode active material, curing the castor oil-based UV oligomer binder so that the composite material is coated on at least a portion of the surface of the positive electrode active material to obtain the composite positive electrode material.

[0142] The castor oil-based UV oligomer adhesive can be selected from the castor oil-based UV oligomer adhesive described in the first aspect. The implementation of the castor oil-based UV oligomer adhesive has been described and illustrated in detail above, and will not be repeated here.

[0143] Castor oil-based UV oligomer binders not only have good bonding properties, but also can form a tight cross-linking network after UV curing, thereby improving the cohesion of the positive electrode film layer. As a result, not only the structural stability of the composite positive electrode material can be improved, but also the structural stability of the positive electrode sheet can be improved, thereby improving the cycle performance of the battery and extending the cycle life of the battery. In addition, castor oil-based UV oligomer binders also have good electrical conductivity. As a result, the electron transfer rate of the composite positive electrode material can be improved, thereby reducing the bulk impedance of the composite positive electrode material, thereby improving the cycle performance, storage performance and rate performance of the battery.

[0144] In some embodiments, the mass ratio of the particles containing M element to the lithium ion conductor material may be 1:0.3-1:0.6.

[0145] Without intending to be limited by any theory or explanation, when the mass ratio of the particles containing M single substance to the lithium ion conductor material meets the given range, an appropriate amount of lithium ion conductor material can be attached to the surface of the particles containing M single substance, thereby improving the ionic conductivity of the composite positive electrode material and reducing the risk of RLCs generated on the surface of the positive electrode active material. In addition, when the mass ratio of the particles containing M single substance to the lithium ion conductor material meets the given range, the risk of gelation of the positive electrode slurry can also be reduced, thereby improving the processability of the composite positive electrode material.

[0146] In some embodiments, the mass ratio of the particles containing M element to the castor oil-based UV oligomer binder may be 1:0.1-1:0.3.

[0147] Without intending to be limited by any theory or explanation, when the mass ratio of the particles to the castor oil-based UV oligomer binder satisfies the given range, the lithium ion conductor material can be closely attached to the surface of the particles containing the M element, and the composite material can be firmly anchored on the surface of the positive electrode active material, thereby improving the structural stability of the composite positive electrode material and reducing the bulk impedance of the composite positive electrode material. As a result, the cycle performance, storage performance and rate performance of the battery can be improved.

[0148] Positive electrode

[0149] The third aspect of the embodiment of the present application provides a positive electrode plate, which includes a positive electrode current collector and a positive electrode film layer located on at least one side of the positive electrode current collector. The positive electrode film layer includes the composite positive electrode material of the first aspect, or the composite positive electrode material prepared according to the method of the second aspect.

[0150] The positive electrode plate of the embodiment of the present application includes the composite positive electrode material of the first aspect, or the composite positive electrode material prepared according to the method of the second aspect, and is applied to a secondary battery, so that the secondary battery can have good cycle performance, storage performance and rate performance.

[0151] In some embodiments, the positive electrode film layer may further include a positive electrode conductive agent. The present application has no particular restrictions on the type of the positive electrode conductive agent. As an example, the positive electrode conductive agent includes at least one of superconducting carbon, conductive graphite, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.

[0152] In some embodiments, the positive electrode film layer may further optionally include a positive electrode binder. The present application has no particular restrictions on the type of positive electrode binder. As an example, the positive electrode binder may include at least one of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), vinylidene fluoride-tetrafluoroethylene-propylene terpolymer, vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer, and fluorine-containing acrylic resin.

[0153] In some embodiments, the positive electrode current collector may be a metal foil or a composite current collector. As an example of a metal foil, aluminum foil may be used. The composite current collector may include a polymer material base and a metal material layer formed on at least one surface of the polymer material base. As an example, the metal material may include at least one of aluminum, aluminum alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy. As an example, the polymer material base may include at least one of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS) and polyethylene (PE).

[0154] The positive electrode film layer is usually formed by coating the positive electrode slurry on the positive electrode current collector, drying and cold pressing. The positive electrode slurry is usually formed by dispersing the positive electrode active material, optional conductive agent, optional binder and any other components in a solvent and stirring them uniformly. The solvent can be N-methylpyrrolidone (NMP), but is not limited thereto.

[0155] Battery

[0156] The battery mentioned in the embodiments of the present application may include one or more battery cells to provide a single physical module with higher voltage and capacity. When there are multiple battery cells, the multiple battery cells are connected in series, in parallel or in mixed connection through a busbar component.

[0157] Typically, a battery cell includes an electrode assembly and an electrolyte. The electrode assembly includes a positive electrode, a negative electrode, and a separator. During the charge and discharge process of the battery cell, active ions (such as lithium ions) are embedded and removed back and forth between the positive electrode and the negative electrode. The separator is arranged between the positive electrode and the negative electrode, which can prevent the positive and negative electrodes from short-circuiting and allow active ions to pass through. The electrolyte plays the role of conducting active ions between the positive electrode plate and the negative electrode plate.

[0158] [Positive electrode]

[0159] In the battery cell of the embodiment of the present application, the positive electrode sheet of the electrode assembly may include the positive electrode sheet of the third aspect. The implementation of the positive electrode sheet has been described and illustrated in detail above, and will not be repeated here. It can be understood that the battery cell of the embodiment of the present application can achieve the beneficial effects of any of the above implementations of the positive electrode sheet of the embodiment of the present application.

[0160] [Negative electrode]

[0161] The negative electrode sheet may include a negative electrode current collector and a negative electrode film layer disposed on at least one side of the negative electrode current collector and including a negative electrode active material. For example, the negative electrode current collector has two surfaces opposite to each other in its thickness direction, and the negative electrode film layer is disposed on any one or both of the two opposite surfaces of the negative electrode current collector.

[0162] The negative electrode active material may adopt the negative electrode active material for secondary batteries known in the art. As an example, the negative electrode active material may include but is not limited to at least one of natural graphite, artificial graphite, soft carbon, hard carbon, silicon-based materials, tin-based materials and lithium titanate. The silicon-based material may include at least one of elemental silicon, silicon oxide, silicon-carbon composite, silicon-nitrogen composite and silicon alloy material. The tin-based material may include at least one of elemental tin, tin oxide and tin alloy material.

[0163] In some embodiments, the negative electrode film layer may further include a negative electrode conductive agent. The present application has no particular restrictions on the type of the negative electrode conductive agent. As an example, the negative electrode conductive agent may include at least one of superconducting carbon, conductive graphite, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.

[0164] In some embodiments, the negative electrode film layer may further include a negative electrode binder. The present application has no particular restrictions on the type of the negative electrode binder. As an example, the negative electrode binder may include at least one of styrene-butadiene rubber (SBR), water-soluble unsaturated resin SR-1B, aqueous acrylic resin (e.g., polyacrylic acid PAA, polymethacrylic acid PMAA, sodium polyacrylate PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA), and carboxymethyl chitosan (CMCS).

[0165] In some embodiments, the negative electrode film layer may further include other additives. As an example, the other additives may include a thickener, such as sodium carboxymethyl cellulose (CMC-Na), a PTC thermistor material, and the like.

[0166] In some embodiments, the negative electrode current collector may be a metal foil or a composite current collector. As an example of a metal foil, a copper foil may be used. The composite current collector may include a polymer material base layer and a metal material layer formed on at least one surface of the polymer material base layer. As an example, the metal material may include at least one of copper, copper alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy. As an example, the polymer material base layer may include at least one of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS) and polyethylene (PE).

[0167] The negative electrode film layer is usually formed by coating the negative electrode slurry on the negative electrode current collector, drying and cold pressing. The negative electrode slurry is usually formed by dispersing the negative electrode active material, optional conductive agent, optional binder, and other optional auxiliary agents in a solvent and stirring them evenly. The solvent can be N-methylpyrrolidone (NMP) or deionized water, but is not limited thereto.

[0168] The negative electrode plate does not exclude other additional functional layers besides the negative electrode film layer. For example, in some embodiments, the negative electrode plate also includes a conductive primer layer (e.g., composed of a conductive agent and a binder) sandwiched between the negative electrode current collector and the negative electrode film layer and disposed on the surface of the negative electrode current collector. In some embodiments, the negative electrode plate of the present application also includes a protective layer covering the surface of the negative electrode film layer.

[0169] [Isolation film]

[0170] The separator is disposed between the positive electrode sheet and the negative electrode sheet to play a role of isolation. The embodiment of the present application has no particular limitation on the type of separator, and any known porous structure separator with good chemical stability and mechanical stability can be selected.

[0171] In some embodiments, the material of the isolation membrane can be selected from one or more of glass fiber, non-woven fabric, polyethylene, polypropylene and polyvinylidene fluoride. The isolation membrane can be a single-layer film or a multi-layer composite film. When the isolation membrane is a multi-layer composite film, the materials of each layer are the same or different, without special restrictions.

[0172] [Electrolytes]

[0173] The electrolyte plays a role in conducting ions between the positive electrode and the negative electrode. The present application embodiment has no specific restrictions on the type of electrolyte, which can be selected according to needs. For example, the electrolyte can be liquid or gel.

[0174] In some embodiments, the electrolyte is an electrolyte solution, which includes an electrolyte salt and a solvent.

[0175] In some embodiments, the electrolyte salt can be selected from at least one of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium perchlorate, lithium hexafluoroarsenate, lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethanesulfonyl)imide, lithium trifluoromethanesulfonate, lithium difluorophosphate, lithium difluorooxalatoborate, lithium dioxalatoborate, lithium difluorodioxalatophosphate, and lithium tetrafluorooxalatophosphate.

[0176] In some embodiments, the solvent can be selected from at least one of ethylene carbonate, propylene carbonate, ethyl methyl carbonate, diethyl carbonate, dimethyl carbonate, dipropyl carbonate, methyl propyl carbonate, ethyl propyl carbonate, butylene carbonate, fluoroethylene carbonate, methyl formate, methyl acetate, ethyl acetate, propyl acetate, methyl propionate, ethyl propionate, propyl propionate, methyl butyrate, ethyl butyrate, 1,4-butyrolactone, cyclopentane sulfone, dimethyl sulfone, methyl ethyl sulfone and diethyl sulfone.

[0177] In some embodiments, the electrolyte may further include additives, such as negative electrode film-forming additives, positive electrode film-forming additives, and additives that can improve certain battery properties, such as additives that improve battery overcharge performance, additives that improve battery high or low temperature performance, etc.

[0178] In some embodiments, the positive electrode sheet, the separator, and the negative electrode sheet may be formed into an electrode assembly by a winding process or a lamination process.

[0179] In some embodiments, the battery cell further includes a housing for accommodating the electrode assembly and the electrolyte. The housing of the battery cell may be a hard shell, such as a hard plastic shell, an aluminum shell, a steel shell, etc. The housing of the battery cell may also be a soft package, such as a bag-type soft package. The material of the soft package may be plastic, and examples of the plastic include polypropylene, polybutylene terephthalate, and polybutylene succinate.

[0180] The embodiment of the present application has no particular limitation on the shape of the battery cell, which can be cylindrical, square or any other shape. Figure 3 The battery cell 5 is a square structure as an example.

[0181] In some embodiments, reference Figure 4, the shell may include a shell 51 and a cover plate 53. Among them, the shell 51 may include a bottom plate and a side plate connected to the bottom plate, and the bottom plate and the side plate enclose a receiving cavity. The shell 51 has an opening connected to the receiving cavity, and the cover plate 53 can be covered on the opening to close the receiving cavity. The positive electrode sheet, the negative electrode sheet and the isolation membrane can form an electrode assembly 52 through a winding process or a lamination process. The electrode assembly 52 is encapsulated in the receiving cavity. The electrolyte is infiltrated in the electrode assembly 52. ​​The number of electrode assemblies 52 contained in the battery cell 5 can be one or more, and those skilled in the art can select according to specific actual needs.

[0182] The preparation method of the battery cell of the embodiment of the present application is well known. In some embodiments, the electrode assembly can be placed in a housing, and after drying, an electrolyte can be injected, and the battery cell can be obtained through vacuum packaging, standing, forming, shaping and other processes.

[0183] In some embodiments, the battery mentioned in the embodiments of the present application refers to a single physical module including one or more battery cells to provide higher voltage and capacity. For example, the battery mentioned in the embodiments of the present application can be a battery module or a battery pack. The battery generally includes a box for encapsulating one or more battery cells. The box can prevent liquid or other foreign matter from affecting the charging or discharging of the battery cells.

[0184] In some embodiments, there may be multiple battery cells in the battery, and the multiple battery cells may be connected in series, in parallel, or in a hybrid connection. A hybrid connection means that the multiple battery cells are both connected in series and in parallel. The multiple battery cells may be directly connected in series, in parallel, or in a hybrid connection, and then the whole formed by the multiple battery cells is accommodated in the box; of course, multiple battery cells may be first connected in series, in parallel, or in a hybrid connection to form a battery module, and then the multiple battery modules are connected in series, in parallel, or in a hybrid connection to form a whole, and then accommodated in the box.

[0185] Figure 5 FIG. 4 is a schematic diagram of a battery module 4 as an example. Figure 5 As shown, there are multiple battery cells 5, and the multiple battery cells 5 are first connected in series, in parallel, or in mixed connection to form a battery module 4. The multiple battery cells 5 in the battery module 4 can be electrically connected through a busbar component to realize the series connection, parallel connection, or mixed connection of the multiple battery cells 5 in the battery module 4. In the battery module 4, the multiple battery cells 5 can be arranged in sequence along the length direction of the battery module 4. Of course, they can also be arranged in any other manner. Further, the multiple battery cells 5 can be fixed by fasteners.

[0186] In some embodiments, the battery modules described above may also be assembled into a battery pack, and the number of battery modules contained in the battery pack may be adjusted according to the application and capacity of the battery pack.

[0187] Figure 6 and Figure 7 is a schematic diagram of a battery pack 1 as an example. Figure 6 and Figure 7 As shown, the battery pack 1 may include a box body and a plurality of battery modules 4 disposed in the box body. The plurality of battery modules 4 in the battery pack 1 may be electrically connected through a busbar component to achieve series connection, parallel connection, or mixed connection of the plurality of battery modules 4 in the battery pack 1. The box body includes an upper box body 2 and a lower box body 3, wherein the upper box body 2 is used to cover the lower box body 3 and form a closed space for accommodating the battery modules 4. The plurality of battery modules 4 may be arranged in the battery box in any manner.

[0188] Electrical devices

[0189] The embodiment of the present application also provides an electric device, the electric device includes a battery cell provided in the embodiment of the present application, and the battery cell is used to provide electrical energy. The battery cell can be used as a power source for the electric device, and can also be used as an energy storage unit for the electric device. The electric device may include mobile devices (such as mobile phones, laptops, etc.), electric vehicles (such as pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks, etc.), electric trains, ships and satellites, energy storage systems, etc., but are not limited thereto.

[0190] As the electrical device, a battery cell, a battery module including a plurality of battery cells, or a battery pack may be selected according to its usage requirements.

[0191] Figure 8 The power consumption device is taken as an example. The power consumption device is a pure electric vehicle, a hybrid electric vehicle, or a plug-in hybrid electric vehicle. In order to meet the requirements of the power consumption device for high power and high energy density, a battery pack or a battery module can be used.

[0192] As another example, the power-consuming device may be a mobile phone, a tablet computer, a notebook computer, etc. Such a device is usually required to be light and thin, and a battery cell may be used as a power source.

[0193] Example

[0194] Hereinafter, the embodiments of the present application will be described. The embodiments described below are exemplary and are only used to explain the present application, and should not be construed as limiting the present application. If no specific techniques or conditions are indicated in the embodiments, the techniques or conditions described in the literature in this area or the product specifications are used. If the manufacturer is not indicated in the reagents or instruments used, they are all conventional products that can be obtained commercially.

[0195] Example 1

[0196] Preparation of composite cathode materials

[0197] The particles containing M element (S element particles) with a volume distribution particle size Dv50 of 1 μm, the lithium ion conductor material (lithium zinc germanate) and the binder (castor oil-based UV oligomer binder) were mixed and ball-milled in a mass ratio of 3.6:90:6.4 to obtain a slurry containing a composite material. The ionic conductivity δ of the lithium ion conductor material is 1.2×10 -2 S / cm, in the binder, the molecular weight of the castor oil-based UV oligomer is 500Da.

[0198] The slurry is mixed with the positive electrode active material LiNi 0.9 Co 0.05 Mn 0.05 After the (NCM955) is evenly mixed, the castor oil-based UV oligomer binder is cured under ultraviolet light so that the composite material is coated on at least part of the surface of the positive electrode active material to obtain a composite positive electrode material. Based on the total mass of the composite positive electrode material, the mass percentage w1 of the particles containing the M single substance is 0.02%, and the mass percentage w2 of the lithium ion conductor material is 0.5%.

[0199] Preparation of positive electrode

[0200] The composite positive electrode material, the conductive agent acetylene black, and the binder polyvinylidene fluoride (PVDF) are uniformly mixed in a proper amount of solvent N-methylpyrrolidone (NMP) at a mass ratio of 96.5:1.5:2 to obtain a positive electrode slurry; the positive electrode slurry is coated on the positive electrode current collector aluminum foil, and the positive electrode sheet is obtained through processes such as drying, cold pressing, slitting, and cutting.

[0201] Preparation of negative electrode

[0202] The negative electrode active material artificial graphite, silicon oxide, conductive agent acetylene black, binder styrene butadiene rubber (SBR) and sodium carboxymethyl cellulose (CMC) are mixed uniformly in a proper amount of solvent deionized water at a mass ratio of 90:5:2:2:1 to obtain a negative electrode slurry; the negative electrode slurry is coated on the negative electrode current collector copper foil, and the negative electrode sheet is obtained through the processes of drying, cold pressing, slitting and cutting.

[0203] Preparation of isolation membrane

[0204] A polyethylene film is used as the isolation film.

[0205] Preparation of electrolyte

[0206] Lithium salt (LiPF6 and LiFSI mixed in a mass ratio of 2:8) was dissolved in a solvent prepared by ethylene carbonate (EC), ethyl methyl carbonate (EMC), and diethyl carbonate (DEC) in a volume ratio of 1:1:1 to obtain an electrolyte with a lithium salt concentration of 1 mol / L.

[0207] Preparation of secondary batteries

[0208] The positive electrode sheet, the separator, and the negative electrode sheet are stacked and wound in order to obtain an electrode assembly; the electrode assembly is placed in an outer package, and after drying, the electrolyte is injected, and after vacuum packaging, standing, forming, shaping and other processes, a secondary battery is obtained.

[0209] Example 2-19

[0210] Based on the preparation process of the composite positive electrode material in Example 1, the type of positive electrode active material, the type of particles containing M simple substance, the volume distribution particle size Dv50 of the particles containing M simple substance, the type of lithium ion conductor material, the type of binder, w1, and w2 are adjusted as shown in Table 1 to prepare the composite positive electrode materials of Examples 2-19. Among them, the adjustment of w1 and w2 can be achieved by adjusting the amount of at least one of the positive electrode active material, the particles containing M simple substance, and the lithium ion conductor material. The positive electrode active material of Example 18 is LiNi 0.9 Co 0.05 Al 0.05 (NCA955).

[0211] The preparation of the positive electrode sheet, negative electrode sheet, separator, electrolyte and secondary battery of Examples 2-19 is the same as that of Example 1.

[0212] Comparative Example 1-2

[0213] Based on the preparation process of the composite positive electrode material in Example 1, the preparation parameters of the composite positive electrode material were adjusted as shown in Table 1 to prepare the composite positive electrode material of Comparative Example 1-2.

[0214] The preparation of the positive electrode sheet, negative electrode sheet, separator, electrolyte and secondary battery of Comparative Example 1-2 is the same as that of Example 1.

[0215] Test Section

[0216] (1) Initial DCR test

[0217] At 25°C, the secondary battery was charged at a constant current of 0.33C to 4.25V, then charged at a constant voltage of 4.25V to a cutoff current of 0.05C, left to stand for 5 minutes, and then discharged at a constant current of 0.33C to a termination voltage of 2.8V to obtain an initial discharge capacity C0.

[0218] At 25°C, the secondary battery was left to stand for 30 minutes, then charged to 4.25V at a constant current of 0.33C0, then charged to a cut-off current of 0.05C0 at a constant voltage of 4.25V, left to stand for 10 minutes, then discharged to 50% SOC at a constant current of 0.33C0, left to stand for 60 minutes, and the voltage at this time was recorded as U0. Then, it was discharged at a rate of 4C0 for 10 seconds, and the voltage U at the 10th second of discharge was recorded. Calculate the initial DCR of the battery = (U-U0) / current corresponding to the 4C0 rate.

[0219] (2) Storage performance test

[0220] At 25°C, the secondary battery was charged at a constant current of 0.33C to 4.25V, then charged at a constant voltage of 4.25V to a cutoff current of 0.05C, left to stand for 5 minutes, and then discharged at a constant current of 0.33C to a termination voltage of 2.8V to obtain an initial discharge capacity C0.

[0221] The secondary battery was charged to 4.25V at a constant current of 0.33C, then charged to a cut-off current of 0.05C at a constant voltage of 4.25V, and then stored in an environment of 60°C for 60 days. After that, the secondary battery was taken out and cooled to 25°C. At 25°C, it was discharged to 2.8V at a constant current of 0.33C, then charged to a cut-off voltage of 4.25V at a constant current of 0.33C, then charged to a cut-off current of 0.05C at a constant voltage of 4.25V, and then stood for 5 minutes, and discharged to a cut-off voltage of 2.8V at a constant current of 0.33C, and the discharge capacity C after high temperature storage was obtained. 60 . Storage capacity retention rate of secondary battery = C 60 / C0×100%.

[0222] Then, at 25°C, the secondary battery was left to stand for 30 minutes, then charged to 4.25V at a constant current rate of 0.33C, then charged to a cutoff current of 0.05C at a constant voltage rate of 4.25V, left to stand for 10 minutes, and then discharged to 50% SOC at a constant current rate of 0.33C, left to stand for 60 minutes, and the voltage at this time was recorded as U a Then, discharge at a rate of 4C for 10 seconds and record the voltage U at the 10th second of discharge. b .

[0223] Calculate the battery storage DCR = (U a -U b ) / 4C rate corresponding current. Storage DCR growth rate of secondary battery = (storage DCR-initial DCR) / initial DCR×100%.

[0224] (3) Cyclic performance test

[0225] Keep the secondary battery at 45℃ for 2h, let it stand for 5min, then charge it to 4.25V at a constant current of 1 / 3C, then charge it to a cut-off current of 0.05C at a constant voltage of 4.25V, let it stand for 5min, discharge it to 2.8V at a constant current of 0.5C, let it stand for 5min, this is a charge and discharge cycle. Repeat the above steps for the same secondary battery, record the discharge capacity D0 of the first cycle and the discharge capacity D of the 2000th cycle. 2000 . Cycle capacity retention rate P of secondary battery 2000 =D 2000 / D0×100%.

[0226] (4) Rate performance test

[0227] At 25°C, the secondary battery was charged to 4.25V at a constant current of 0.33C, then charged to a cut-off current of 0.05C at a constant voltage of 4.25V, left to stand for 5 minutes, and then discharged to a termination voltage of 2.8V at a constant current of 0.33C, to obtain an initial discharge capacity of C0. After standing for 5 minutes, the secondary battery was charged to 4.25V at a constant current of 0.33C, then charged to a cut-off current of 0.05C at a constant voltage of 4.25V, left to stand for 5 minutes, and then discharged to 2.8V at a rate of 1C, to obtain a discharge capacity of C1 at a rate of 1C; then charged to 4.25V at a constant current of 0.33C, then charged to 0.05C at a constant voltage, left to stand for 5 minutes, and then discharged to 2.8V at a rate of 2C, to obtain a discharge capacity of C2 at a rate of 2C.

[0228] 1C capacity retention rate = C1 / C0×100%

[0229] 2C capacity retention rate = C2 / C0×100%

[0230] The larger the 1C capacity retention rate and the 2C capacity retention rate, the better the rate performance of the battery.

[0231] The test results are shown in Table 2.

[0232] Table 1

[0233]

[0234] Table 2

[0235]

[0236] From the test results of Table 1 and Table 2, it can be seen that the composite positive electrode material of the embodiment of the present application has a specific structure and composition, which can effectively reduce the DCR of the battery and improve the cycle performance, rate performance and storage performance of the battery.

[0237] In contrast, in Comparative Example 1-2, sulfur is used to coat the positive electrode active material, and the DCR of the battery is relatively high, and the cycle performance, rate performance and storage performance are far inferior to those of Example 1-19.

[0238] For some compounds given but not listed in the embodiments, since their chemical properties and reaction properties when participating in electrochemical reactions are similar to those of the compounds listed in the embodiments, they are all suitable for the technical scheme of the present invention and are therefore not listed one by one here.

[0239] It should be noted that the present application is not limited to the above-mentioned embodiments. The above-mentioned embodiments are only examples, and the embodiments having the same structure as the technical idea and exerting the same effect within the scope of the technical solution of the present application are all included in the technical scope of the present application. In addition, without departing from the scope of the main purpose of the present application, various modifications that can be thought of by those skilled in the art to the embodiments and other methods of combining some of the constituent elements in the embodiments are also included in the scope of the present application.

Claims

1. A composite positive electrode material, include: Positive electrode active material; as well as A coating layer is coated on at least part of the surface of the positive electrode active material, wherein the coating layer comprises a composite material, The composite material includes particles containing a simple substance M and a lithium ion conductor material attached to the surface of the particles containing the simple substance M, wherein M includes at least one of S, Se and Te.

2. The composite cathode material according to claim 1, in, The lithium ion conductor material includes an ion conductivity of 1×10 -5 S / cm or above, and can be selected as a lithium ion conductor material of 0.001S / cm-1S / cm.

3. The composite positive electrode material according to claim 1 or 2, in, The lithium ion conductor material includes at least one of lithium zinc germanate, lithium aluminum titanium phosphate, lithium aluminum germanium phosphate, lithium lanthanum titanate, glassy lithium conductive electrolyte powder, and garnet structure lithium conductive electrolyte powder; Optionally, the lithium ion conductor material includes at least one of lithium aluminum titanium phosphate and lithium aluminum germanium phosphate.

4. The composite cathode material according to any one of claims 1 to 3, in, The volume distribution particle size Dv50 of the particles containing the M element is ≤ 2 μm, and can be selected to be 0.3 μm-1 μm; and / or The volume distribution particle size Dv50 of the lithium ion conductor material is ≤100nm, and can be selected to be 20nm-50nm; and / or The volume distribution particle size Dv50 of the positive electrode active material is 5 μm-15 μm; and / or The volume distribution particle size Dv50 of the composite positive electrode material is 8 μm-20 μm.

5. The composite cathode material according to any one of claims 1 to 4, in, Based on the total mass of the composite positive electrode material, The mass percentage of the positive electrode active material is 80%-98%, and can be 90%-95%; and / or The mass percentage of the particles containing M single substance is 0.02%-5%, and can be 0.05%-2%; and / or The mass percentage of the lithium ion conductor material is 0.01%-1%, and can be optionally 0.05%-1%.

6. The composite cathode material according to any one of claims 1 to 5, in, The composite material is attached to the surface of the positive electrode active material through a binder to form the coating layer; Optionally, the lithium ion conductor material is attached to the surface of the particles containing the M element through the binder.

7. The composite positive electrode material according to claim 5, in, The adhesive comprises a castor oil-based UV oligomer adhesive; Optionally, the castor oil-based UV oligomer adhesive includes a castor oil-based UV oligomer having a molecular weight of 200Da-800Da.

8. The composite cathode material according to any one of claims 1 to 7, in, The positive electrode active material includes a nickel-cobalt-manganese ternary material and / or a nickel-cobalt-aluminum ternary material; Optionally, in the nickel-cobalt-manganese ternary material, the molar content of Ni element in the transition metal element is greater than or equal to 0.6; Optionally, in the nickel-cobalt-aluminum ternary material, the molar content of Ni element in the transition metal elements is greater than or equal to 0.

6.

9. A method for preparing a composite positive electrode material, include: Preparing a composite material, comprising mixing particles containing a simple substance M with a lithium ion conductor material, and allowing the lithium ion conductor material to adhere to the surface of the particles containing a simple substance M, to obtain a composite material, wherein M comprises at least one of S, Se, and Te; The preparation of the composite positive electrode material comprises uniformly mixing the composite material with the positive electrode active material, and coating the composite material on at least a part of the surface of the positive electrode active material to obtain the composite positive electrode material.

10. The method according to claim 9, in, The preparation of the composite material comprises: mixing the particles containing the M element, the lithium ion conductor material and the castor oil-based UV oligomer binder and ball milling them to obtain a slurry containing the composite material; The preparation of the composite positive electrode material comprises: after uniformly mixing the slurry and the positive electrode active material, curing the castor oil-based UV oligomer binder so that the composite material is coated on at least a portion of the surface of the positive electrode active material to obtain the composite positive electrode material.

11. The method according to claim 10, in, The mass ratio of the particles containing M element to the lithium ion conductor material is 1:0.3-1:0.6; and / or The mass ratio of the particles containing M element to the castor oil-based UV oligomer adhesive is 1:0.1-1:0.

3.

12. A positive electrode sheet, comprising a positive electrode current collector and a positive electrode film layer located on at least one side of the positive electrode current collector, wherein the positive electrode film layer comprises the composite positive electrode material according to any one of claims 1 to 8, or the composite positive electrode material prepared by the method according to any one of claims 9 to 11.

13. A battery comprising the positive electrode sheet according to claim 12.

14. An electrical device comprising the battery according to claim 13.

Citation Information

Patent Citations

  • Carbon-sulfur-shell matter composite material having network dual-core shell structure and preparation method thereof

    CN103474633A

  • Preparation method of lithium-ion-conductor-coated sulfur lithium positive electrode material containing zirconium titanium phosphate

    CN108346785A

  • Selenium-coated high-nickel ternary layered positive electrode material and preparation method thereof

    CN110668509A

  • Application of castor oil-based UV oligomer and lithium-sulfur battery positive electrode prepared from castor oil-based UV oligomer

    CN112646120A

  • Low-temperature vapor deposition coated high-nickel ternary layered positive electrode material and preparation method thereof

    CN112768662A

Cited By

  • Composite positive electrode material and preparation method therefor, positive electrode sheet comprising same, battery, and electric device

    EP4723188A1